Effect of various factors on extraction efficiency of total anthocyanins from Butterfly pea (Clitoria ternatea L. Flowers) in Southern Vietnam - Pham, Tri Nhut; Lam, Tri Duc; Nguyen, Minh Tien; Le, Xuan Tien; Vo, Dai-Viet N.; Toan, Tran Quoc; Vo, Thanh Sang (IOP Publishing, 2019)
Nowadays, anthocyanins have become an interesting topic of much scientific research and act as potential sources of eco-friendly natural food dyes and their helpful effects on human health.. The purpose of the present article was to apply conventional extraction methods of pigments from Butterfly pea (Clitoria ternatea L.Flowers) in Southern Vietnam were tested to extract anthocyanins. The effects of various factors, including the solvent concentration, extraction time, temperature, and solvent/material ratio on the extraction total anthocyanins from Butterfly pea were investigated. In this study, the concentration of monomeric anthocyanins was completed by the spectrophotometry pH differential method.The highest recovered anthocyanin level was achieved with 50 % ethanol (143.49 mg/L), while the lowest one was obtained with water (90.9 mg/L). The extraction yield was significantly affected by temperature and the excellent condition was 60°C. The extraction yield raised with increasing of solvent/material ratio until equilibrium has arrived at the optimal ratio of 25:1 (mL/g). The extraction yield increased first and then decreased with an extension in time values.